The SAGE handbook of grounded theory - Bryant, Antony, 1953-; Charmaz, Kathy, 1939- (SAGE, 2007)
Recent surveys have shown that grounded theory is by far the most popular qualitative method across a range of disciplines. Edited by two of the foremost writers in the field, this book provides an overview of the field and brings together and represents all of the major standpoints within grounded theory.